Pemberdayaan Masyarakat Desa Wisata Tunjungan Melalui Bimtek Peningkatan Kapasitas dan Kapabilitas Sumber Daya Manusia Pariwisata Tunjungan - Artin Bayu Mukti; Dwi Budi Santoso; Azis Nur Rosyid (Karunia: Jurnal Hasil Pengabdian Masyarakat Indonesia, 2023)
The development and progress of tourist attractions, in this case a tourist village, are largely determined by the readiness of their human resources, especially tour guides, especially from a technical point of view. Guides, from a technical and communication point of view, are increasingly able to captivate visitors, making them feel at home more and more. In addition, tourism product marketing that has not been maximized, especially the promotion of tourism products through digital media, has slightly hampered the introduction of tourism village products where the role of digital marketing is so important, especially those based on the web and social media. Recognizing such a mindset, the solution offered is to hold education and training (training) along with mentoring for tourism HR in the Tunjungan Tourism Village. Provision and capacity building according to the Indonesian National Work Competency Standards (SKKNI) absolutely must be provided, covering knowledge, skills, and attitude. As well as being given knowledge about the basics of excellent service and tour guides. Tunjungan Tourism Village Community Empowerment Through Technical Guidance Capacity building and Capability of Tourism human resources, which has been implemented, has resulted in the participation of participants (the target audience) who expressed satisfaction and enthusiasm. Participants (the target audience) also hope that in the following year there will be ongoing activities to increase knowledge, skills, and attitudes for tourism HR in the Tunjungan Tourism Village.